Effects of Supplementation of Vitamin A on some Aspects of Lung Fuctions in Elderly Women of a Rural Area of Bangladesh (TAJ: Journal of Teachers Association, 2009)
The study was carried out to observe the changes in lung functions in the elderly women bothbefore and two months after supplementation of vitamin A. For this purpose, a total number of30 apparently healthy elderly female subjects with age ranging from 40-60 years were selectedfrom a rural area of Bangladesh. They were studied both before and two months aftersupplementation of vitamin A at a dose of 10,000 IU daily. Sex matched 30 apparently healthyadult subjects with age ranging from 25-40 years were taken as control. Pulmonary functionswere assessed by measuring FVC, FEVi, FEVi/FVC% and PEFR by VM1 ventilometer onstanding position.The mean measured pulmonary variables such as FVC, FEVi, FEV,/FVC% and PEFR were lowerthan those of their predicted values both in the experimental and control groups. The meanmeasured values of all the pulmonary variables were significantly lower in the elderly subjectscompared with those of the younger age group. Again, the FVC, FEVi, FEVi/FVC% and PEFRwere significantly increased in the same group of subjects after supplementation of vitamin A.But not up to the level of those of younger subjects.The result of the study reveals that pulmonary functions become lower in the elderly subject'simprovement of which occurs after supplementation of vitamin A. These lower pulmonaryfunctions in the elderly subjects of the present study group is likely to be due to low dietaryintake of vitamin A as pulmonary functions were improved after supplementation of vitamin A.doi: 10.3329/taj.v16i2.3886TAJ December 2003; Vol.16(2): 68-72